PENGEMBANGAN BAHAN AJAR KONSEP DASAR IPA TERINTEGRASI NILAI-NILAI KEISLAMAN - Arda; Ardiansyah (Koordinat Jurnal MIPA, 2023)
This research is development research. It adapts the 4D development model from Thiagarajan which consists of define, design, develop and disseminate. It aims to develop of teaching materials for basic concepts of natural science integrated with Islamic values. Subjects of this research were students of Natural Sciences Education Study Program. The research instrument used consisted of expert validation sheets and student response questionnaires. This research uses quantitative and qualitative data analysis. The results showed that the stages of developing teaching materials were carried out up to the develop stage. The results of the validator's analysis of the feasibility of teaching materials obtained a percentage of 94.55%. This shows that the teaching materials that have been developed are very feasible to be tested and used in learning the Basic Concepts of Natural Science Course. The student response questionnaire assessment showed an acquisition of 4.47 with a percentage of 89.4%, which means that students gave a very good response to the teaching materials that had been developed. Comments given by students in the questionnaire also show that the teaching materials that have been developed are interesting and the material presented is relevant to everyday life.